2018
DOI: 10.1177/0269215518766642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mirror therapy on walking ability, balance and lower limb motor recovery after stroke: a systematic review and meta-analysis of randomized controlled trials

Abstract: The systematic review demonstrates that the use of mirror therapy in addition to some form of rehabilitation appears promising for some areas of lower limb function, but there is not enough evidence yet to suggest when and how to approach this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
(74 reference statements)
0
32
0
Order By: Relevance
“…The PEDro scale consisted of 11 items. One item on the PEDro scale (eligibility criteria) is related to external validity and is generally not used to calculate the method score ( 41 , 42 ). Therefore, a score of 0–10 was allocated to each study (9–10: excellent; 6–8: good; 4–5: fair; and ≤ 3: poor) ( 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PEDro scale consisted of 11 items. One item on the PEDro scale (eligibility criteria) is related to external validity and is generally not used to calculate the method score ( 41 , 42 ). Therefore, a score of 0–10 was allocated to each study (9–10: excellent; 6–8: good; 4–5: fair; and ≤ 3: poor) ( 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, studies conducted in stroke patients with hemiplegia after ictus showed that mirror therapy could significantly rehabilitate patients with upper limb motor dysfunction ( Yavuzer et al, 2008 ; Nogueira et al, 2021 ; Zhuang et al, 2021 ). In addition, the role and impact of mirror therapy have also been explored in lower limb motor rehabilitation ( Sütbeyaz et al, 2007 ; Li et al, 2018 ; Louie et al, 2019 ). Compared with the control group, the lower limb motor function and the daily living activities in the mirror group were significantly improved ( Gandhi et al, 2020 ).…”
Section: Mirror Therapymentioning
confidence: 99%
“…Other studies used further approaches such as circuit based exercises, strength training or backward walking training or mirror therapy to improve balance after stroke [ 13 , 16 18 ]. It can therefore be argued that our balance exercises were somewhat static and not dynamic.…”
Section: Main Textmentioning
confidence: 99%